Determinants of Customs Fraud and Corruption Evidence from Two African Countries - Stasavage, David (OECD Development Centre Working Papers, 1998)
Corruption in customs administrations is a major problem in many African countries. Data from the period 1990-96 are used to examine several hypotheses concerning the determinants of customs fraud in Senegal and Mali. Statistical tests using product-by-product data support the widely held view that high levels of taxation lead to fraud. The findings also show that hiring a pre-shipment inspection company can be an effective tool in fighting corruption, but only if it is accompanied by internal reforms like computerisation of customs procedures. Finally, changes in determinants of corruption, such as levels of taxation, have themselves depended upon broader political changes in each of the two countries ...